Isolation, purification and characterization of a 'factor' from Fusarium oxysporum responsible for platinum nanoparticle formation - Govender, Yageshni (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
Nanoparticles are microscopic particles in the nanometre range of between 1-100 nm. A wide variety of metal nanoparticles have been found to be produced by prokaryotic and eukaryotic organisms including several fungal species, when exposed to solutions containing metal salts. Previous studies have suggested that this bioreduction of metal particles may occur via an active reductase/hydrogenase enzyme process where H2 is the electron donor and positively charged platinum species act as the electron acceptors becoming reduced to a neutral metal nanoparticle. In view of this on going research, the current study investigated the "factors" in the fungus Fusarium oxysporum which were responsible for platinum nanoparticle formation. The fungus F.oxysporum was used in this study as it has been previously shown to produce a variety of nanoparticles including gold and silver. During exposure of the biomass to H2PtCl6 the initial response to the platinum salts was metal internalisation and subsequent reduction of H2PtCI6 to produce platinum nanoparticles. The observed localization and distribution of platinum precipitates provided some evidence for a hydrogenase mediated bioreduction of platinum salts to produce nanoparticles. Factors secreted by the fungus into the extracellular fluids, were shown to be responsible for platinum nanoparticle formation. From the identification, purification and characterisation studies it was concluded that a hydrogenase and other "factors" were responsible for platinum nanoparticle formation in F.oxysporum. Purification of the hydrogenase by freeze-drying and Sephacryl S200 size exclusion- ion exchange chromatography revealed the enzyme to be a dimer with a 29.4 and 44.5 kDa when analysed by a 10 % SDS-PAGE. Characterisation of the enzyme revealed optimal activity at a pH of 7.5 and temperature of 38 Â°C while it exhibited a poor thermal stability with a half life of 36 minutes. The kinetic parameters Vmax and Km were 3.16 U ml-1 and 3.64 mM respectively. The purified hydrogenase was used in subsequent experiments for the reduction of platinum salts, H2PtCl6 and PtCl2. the results indicated an over 90 % reduction of the platinum salts and TEM micrographs indicated the production of platinum nanoparticles under the various experimental conditions.
Keywords: Nanoparticles; Platinum; Fusarium oxysporum; Fungi; Hydragenase